2014
DOI: 10.7748/nr2014.01.21.3.8.e1226
|View full text |Cite
|
Sign up to set email alerts
|

Specific design features of an interpretative phenomenological analysis study

Abstract: The distinctive design of this study further emphasises the flexibility of IPA, while simultaneously showing fidelity to the core principles underlying the research methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 0 publications
0
37
0
Order By: Relevance
“…Further details of the research methods can be found in Ref. (Wagstaff & Williams ) and under review.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Further details of the research methods can be found in Ref. (Wagstaff & Williams ) and under review.…”
Section: Design and Methodsmentioning
confidence: 99%
“…There were two rounds of interviews, with a main interview with the seven service users followed by a second ‘clarifying’ interview with six of the service users. For further detail see Wagstaff & Williams (). All the interviews with the participants were audio recorded and professionally transcribed verbatim.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis will attempt to uncover the key themes and meanings that emerge from interviews. IPA appears appropriate to this specific research question, in that it engages in interpretative methodology to access an individual's cognitive inner world, is able to capture convergence and divergence of the lived experiences and furthermore acknowledges the subjective, unique form of experience of one person in a given context in a given point in time (Smith et al ., ; Wagstaff, ). IPA acknowledges that the researcher's involvement with the participant's story has an interpretative element (Murray & Holmes, ).…”
Section: Methodsmentioning
confidence: 99%